The Use of Cake Mobile Application in Learning English Speaking Skills for Young Learners - Mokhamad Azis Aji Abdilah (Indra institute Research & Publication, 2024)
The purpose of this study is to investigate how the Cake Mobile Application might be used as a tool for improving English-speaking skills. The cake mobile application is a smartphone-based application created specifically to make learning English easier. The Cake mobile application has features for learning English to students, such as voice recognition and speech recognition. This study included a review of the literature. A literature study is a method for gathering data that involves researching books, articles, documents, and reports related to problems resolved. The results show that the cake mobile app has many benefits for learning speaking skills, especially for young learners. It can be a way to help young learners get better at speaking in front of others and get their attention. Several suggestions can be made based on the research findings to improve the English language proficiency of young learners through the use of the Cake mobile app: (1) stressing the importance of learning through authentic language use and real-life scenarios to enhance speaking proficiency in real-world situations; (2) integrating speech recognition and AI-driven feedback mechanisms to provide prompt and accurate speaking proficiency assessments; and (3) regularly reviewing and updating app content to ensure that it is relevant and effective in achieving learning goals.